Xylooligosaccharide Supplementation Mitigates Growth Performance Impairment and Intestinal Injuries in Enterohemorrhagic Escherichia coli-Challenged Broilers - Qingyun Cao; Yaru Song; Jiarong Fang; Zemin Dong; Changming Zhang; Hui Ye; Jianjun Zuo; Weiwei Wang (The Journal of Poultry Science)
Xylooligosaccharide (XOS) is a typical prebiotic; however, whether it protects chickens from enterohemorrhagic Escherichia coli (EHEC) challenge remains unknown. This study investigated the protective effects of XOS on the growth and gut health of EHEC-challenged broilers. A total of 270 1-day-old broilers were divided into three groups (nine replicates per group): negative control (were not challenged), positive control (EHEC-challenged from days 8 to 11), and XOS (EHEC-challenged broilers supplemented with 1.6 g/kg XOS). Samples were collected from broilers at 14 days. XOS addition alleviated EHEC-induced decline in growth performance, liver index, and the villus height:crypt depth ratio in both the duodenum and ileum of broilers. XOS also attenuated the increase in the relative mRNA expression of the ileal proinflammatory cytokine interleukin 6 and the tight junction protein occludin in EHEC-challenged broilers. Microbiota analysis revealed that EHEC challenge reduced or tended to reduce the abundance of several beneficial bacteria (such as Firmicutes, Fournierella, and Lysinibacillus) and increased or tended to increase the abundance of multiple harmful bacteria (such as Proteobacteria, Aquabacterium, Methylotenera, and Arthrobacter) in the ileum. However, XOS addition mitigated these changes and downregulated or tended to downregulate certain disease-related pathways of the ileal microbiota. In conclusion, XOS supplementation mitigated poor growth performance and intestinal damage in EHEC-challenged broilers, and was probably involved in the attenuation of gut microbiota disturbances that might protect against EHEC infection. These findings provide a basis for the application of XOS to limit the risk of EHEC infection.